Metals Concentrations in Muscle Tissue from Walleye, Smallmouth Bass, and a Sturgeon Collected from Lakes and Rivers within the 1854 Ceded Territory during Fall 2016 - Polkinghorne, Christine N.; Beesley, Kimberly M.; Markee, Thomas P. (Lake Superior Research Institute, 2017)
Whole fish samples of walleye (Sander vitreus) and smallmouth bass (Micropterus dolomieu), captured during the fall of 2016 from lakes within the 1854 Ceded Territory were analyzed for total mercury (Hg) content at the University of Wisconsin-Superior’s Lake Superior Research Institute (LSRI). Forty three whole walleye and twenty two whole smallmouth bass samples from a total of three lakes were processed and the muscle tissue was analyzed for mercury. A sturgeon (Acipenseridae) that was found near death in the St. Louis River was also collected and the muscle tissue analyzed for total mercury (Hg) content along with nine other metals including: arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), manganese (Mn), selenium (Se), and zinc (Zn).
Keywords: Walleye; Smallmouth bass; Mercury (Hg)